Solvent extraction of Ca2+, Ba2+, Cu2+, Zn2+, Cd2+, Pb2+, UO22+, Mn2+, Co2+ and Ni2+ into nitrobenzene using strontium dicarbol-lylcobaltate and tetra-tert-butyl p-tert-butylcalix[4]arene tetraacetate - E. MAKRLÍK; J. BUDKA; P. VAŇURA; P. SELUCKÝ (Journal of the Serbian Chemical Society, 2008)
The exchange extraction constants corresponding to the general equilibrium M2+(aq) + SrL2+(nb) D ML2+ (nb) + Sr2+ (aq) occurring in the two-phase water–nitrobenzene system (M2+ = Ca2+, Ba2+, Cu2+, Zn2+, Cd2+, Pb2+, UO22+, Mn2+, Co2+ or Ni2+; L = tetra-tert-butyl p-tert-butylcalix[4]arene tetraacetate; aq = aqueous phase; nb = nitrobenzene phase) were evaluated from extraction experiments and -activity measurements. Furthermore, the stability constants of the ML2+ complexes in water saturated nitrobenzene were calculated; they were found to increase in the cation order Ba2+ < Mn2+ < Pb2+, Co2+ < Cu2+, Zn2+ < Cd2+, Ni2+ < UO22+ < Ca2+.